Research on Image Splicing and Fusion Processing Algorithm in Large Visual Field - Jie, Wu; Feng, Zuren; Song, Xiaoru (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
To obtain wide area and a large field of view image, splicing and fusion algorithm is presented. Single image is preprocessed by utilizing rough matching algorithm, which can narrow down the matching range to improve the speed and precision of image stitching and fusion, at the same time, Single image is preprocessed by filter processing algorithm, which will reduce interference noise, improve SNR and enhance the effective character information of image; the best matching position is found by using a combined splicing algorithm, which are ratio template matching algorithm and template matching algorithm, and the images are spliced at the best matching position; we take the neighborhood weighted average fusion algorithm to eliminate the distinct splicing trace. The captured images are processed by using correlation algorithm, a large field of view and high quality image is obtained. The experimental results verify the validity of the algorithm.